2022
DOI: 10.3390/polym14020265
|View full text |Cite
|
Sign up to set email alerts
|

Natural Fillers as Potential Modifying Agents for Epoxy Composition: A Review

Abstract: Epoxy resins as important organic matrices, thanks to their chemical structure and the possibility of modification, have unique properties, which contribute to the fact that these materials have been used in many composite industries for many years. Epoxy resins are repeatedly used in exacting applications due to their exquisite mechanical properties, thermal stability, scratch resistance, and chemical resistance. Moreover, epoxy materials also have really strong resistance to solvents, chemical attacks, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 82 publications
(104 reference statements)
1
38
0
Order By: Relevance
“…The parquet flooring post-production wood flour was applied as reinforcement for epoxy resins based on a polyaddition product of epoxidized soybean oil and bisphenol-A. As presented within this manuscript, previous studies belonging to a wide variety of application-related research focused on the utilization of green fillers such as post-agricultural waste powder, grass fibers, bast/leaf fibers, and other natural fibers as reinforcement for both synthetic and bio-based epoxy resins [ 42 , 59 , 60 ]. The search for the possibility of additional uses continues because the management of waste or post-production particles of natural origin is environmentally friendly due to their sustainability, low cost, and wide availability.…”
Section: Discussionmentioning
confidence: 99%
“…The parquet flooring post-production wood flour was applied as reinforcement for epoxy resins based on a polyaddition product of epoxidized soybean oil and bisphenol-A. As presented within this manuscript, previous studies belonging to a wide variety of application-related research focused on the utilization of green fillers such as post-agricultural waste powder, grass fibers, bast/leaf fibers, and other natural fibers as reinforcement for both synthetic and bio-based epoxy resins [ 42 , 59 , 60 ]. The search for the possibility of additional uses continues because the management of waste or post-production particles of natural origin is environmentally friendly due to their sustainability, low cost, and wide availability.…”
Section: Discussionmentioning
confidence: 99%
“…Epoxies have features that distinguish them from other resins, and adjustments can be made to meet our specifications. Epoxies have superior mechanical qualities, including increased thermal stability, wear and chemical resistance, and resistance to ageing caused by environmental factors [ 22 ]. In order to improve a composite’s specific characteristics and traits, fillers are incorporated into the material.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has concentrated on green fillers such as date seed powders, coconut and cashew nut shell powders, and rice and maize husks. Natural fibers and fillers are used in composites because they are inexpensive, widely available, biodegradable, recyclable, and lightweight [ 22 ]. Researchers are becoming more interested in starch-based bioplastics due to their environmentally beneficial characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The green nature of epoxy resins can also be enhanced by modifying them with fillers [150]. The results of recent research on epoxy resins modified with lignin [151], nanocellulose [152], hemp fibers [153], as well as industrial waste [154] indicated that this trend should develop in the near future.…”
Section: Polyurethane Foamsmentioning
confidence: 99%